2015
DOI: 10.1016/j.vascn.2015.08.153
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vivo corneal trans-epithelial electrical resistance measurement device

Abstract: Purpose: To develop a device that is capable of easily measuring corneal transepithelial electrical resistance (TER) and changes in the corneal barrier function. Methods:We had previously developed an in vivo method for measuring corneal TER using intraocular electrode. This method can be used to precisely measure the decline of the corneal barrier function after instillation of benzalkonium chloride (BAC). In order to lessen the invasiveness of that procedure, we further refined the method for measuring the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…BAC is known to increase tissue permeability and drug bioavailability by affecting tight junction integrity but it can affect tissue viability. 44,46 We confirmed that a significant part of the topical drug formulation's effect on tissue barrier integrity and viability was due to BAC (Table 6). However, since the drug formulation's effects were more pronounced than those observed after treatment with 0.02% BAC in KRB, other components of the commercial vehicle, as well as the drug itself, may contribute to or exacerbate the detrimental effect on tissue viability observed for BAC.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…BAC is known to increase tissue permeability and drug bioavailability by affecting tight junction integrity but it can affect tissue viability. 44,46 We confirmed that a significant part of the topical drug formulation's effect on tissue barrier integrity and viability was due to BAC (Table 6). However, since the drug formulation's effects were more pronounced than those observed after treatment with 0.02% BAC in KRB, other components of the commercial vehicle, as well as the drug itself, may contribute to or exacerbate the detrimental effect on tissue viability observed for BAC.…”
Section: Discussionsupporting
confidence: 57%
“…4). 42,[44][45][46] Light Microscopy and Hematoxylin and Eosin Staining 3D corneal tissues were harvested on day 10, rinsed in PBS, fixed in 10% neutral buffered formalin for 1 hour, dehydrated in a graded series of ethanol, and embedded in paraffin. Fivemicrometer-thick hematoxylin and eosin (H&E)-stained cross sections were prepared using standard histologic techniques 47 and examined with a light microscope (Olympus BX41; Center Valley, PA, USA) or processed using an Olympus VS120 slide scanner at 310 objective with a 30.5 camera adjustment magnification.…”
Section: Transepithelial Electrical Resistance Measurementsmentioning
confidence: 99%
“…This design more accurately reflects the clinical instillation of 11 ophthalmic drugs and provides relevant data about the acute corneal toxicity of some eye drops. [23][24][25][26] Although that previously described corneal TER measurement system in vivo was informative and reliable, it was still invasive and could not be used clinically for human studies because of intraocular electrodes. So, we developed this new less invasive corneal TER measurement method in which one electrode is placed on the surface fluid of the cornea and the other one in the conjunctival fornix.…”
Section: Discussionmentioning
confidence: 99%
“…23 In our previous studies, after developing a new in vivo method of measuring the corneal TER of rabbit corneas, we demonstrated that 0.02% BAC concentration immediately caused acute corneal barrier dysfunction. [23][24][25][26] In this study, we checked the reliability and the efficacy of this new less invasive corneal TER measurement method by measuring the corneal TER changes after application of 0.02% BAC in both rabbits and humans. The results of this new less invasive method agreed with those of the formerly established anterior chamber method used in rabbit experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation